The unusual trading volume and earnings surprises in China's market - Terence Tai-Leung Chong; Yueer Wu; Jue Su (Journal of Risk and Financial Management, 2020)
This study examines the empirical relationship between unusual trading volume and earnings surprises in China's A-share market. We provide evidence that an unusually low trading volume can signify negative information about firm fundamentals. Moreover, unusual trading volumes could predict abnormal returns close to the earnings announcement date. The degree of, and changes in, divergence of opinion could explain this result. Our study provides an insight into China's market, where short sales are strictly forbidden. We report a strong relationship that is quite different from that described in most studies on the United States market.
Keywords: 330; China's market; divergence of opinion; earnings surprises; stock return; unusual trading volume